If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(1 + 6v) = -140 (1 * 4 + 6v * 4) = -140 (4 + 24v) = -140 Solving 4 + 24v = -140 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 24v = -140 + -4 Combine like terms: 4 + -4 = 0 0 + 24v = -140 + -4 24v = -140 + -4 Combine like terms: -140 + -4 = -144 24v = -144 Divide each side by '24'. v = -6 Simplifying v = -6
| 3-4x(2+3x)=1(1+5x) | | 6R+17R+10=0 | | (-35)+x=32 | | -6y+-2x=18 | | 4(n+6)=2(n+5) | | 17-(5m+4)=5+4m-19 | | 4x-8=5(x+6) | | -2(1.7)= | | 3x-23=3-9x | | z-5z=4z-4-z | | x+20+2x=-12x-4 | | -(z+6)+(4z+1)= | | 148=61.412+2.317x | | 3-4(2)=5(2-3) | | .50(2r+4)-.25(16-8r)= | | 2/3x-4 | | 3(5x+1)=10x+13 | | 16t^2+72t=32 | | S=2pi^2+2pirh | | 103.25t=84.5 | | 2a^2-13a+108=0 | | L-12.5=48.6 | | 3x+=25 | | 84.5=103.25 | | n=6.6 | | 0=y-18xy-3y^2 | | 2x^2+150x-7900=0 | | x+n=231 | | -4n+7+6n=11 | | xy=3x-4 | | 6+z=10 | | 2x+3=x^2+3x+2 |